STATUS OF GLYCEMIC CONTROL IN PATIENTS OF TYPE 2 DIABETES MELLITUS: Glycemic Control in Type 2 Diabetes - Khan, Dr. Abid Ullah; Khan, Muhammad Zafar Ali; ., Mansoor Nadeem; Bangash, Rehana Yasmeen; ., Amer Fakhr (Pakistan Armed Forces Medical Journal, 2013)
Objective: To determine the status of glycemic control in patients of type 2 diabetes mellitus.Design: Cross sectional descriptive study.Place and Duration of Study: Medical out-patient/ in -patient departments at Military Hospital Rawalpindi from January 2011 to December 2012.Methods: Six hundred and fifty patients of type 2 DM fulfilling the required criteria were included in the study. Glycemic control of these patients was determined by estimation of blood glucose (fasting and random) and glycosylated haemoglobin (HbA1c). The patients were grouped in three categories good, fair and poor diabetic control having their HbA1c values of being 6-7%, 7.1-8% and more than 8.1% respectively. Statistical package for social sciences (SPSS) version 15 was used for analysis.Results: Out of 650 patients 377 (58%) had poor glycemic control with mean HbA1c of 9.5% ± 0.95, 78 (12%) patients had fair control of glycemic control with mean HbA1c of 7.8 ± 0.25, and 195 (30%) patients had good glycemic control with mean HbA1c of 6.4 ± 0.17.Conclusion: Majority of patients had poor control of their glycemic status which is an important indicator and predictor of both micro and macrovascular complications.